Novel Insights into Regulation of Asparagine Synthetase in Conifers - Canales, Javier; Rueda-López, Marina; Craven-Bartle, Blanca; Avila, Concepción; Cánovas, Francisco M. (Frontiers in Plant Science, 2012)
Asparagine, a key amino acid for nitrogen storage and transport in plants, is synthesized via the ATP-dependent reaction catalyzed by the enzyme asparagine synthetase (AS; EC 6.3.5.4). In this work, we present the molecular analysis of two full-length cDNAs that encode asparagine synthetase in maritime pine (Pinus pinaster Ait.), PpAS1 and PpAS2. Phylogenetic analyses of the deduced amino acid sequences revealed that both genes are class II AS, suggesting an ancient origin of these genes in plants. A comparative study of PpAS1 and PpAS2 gene expression proﬁles showed that PpAS1 gene is highly regulated by developmental and environmental factors, while PpAS2 is expressed constitutively. To determine the molecular mechanisms underpinning the differential expression of PpAS1, the promoter region of the gene was isolated and putative binding sites for MYB transcription factors were identiﬁed. Gel mobility shift assays showed that a MYB protein from Pinus taeda (PtMYB1) was able to interact with the promoter region of PpAS1. Furthermore, transient expression analyses in pine cells revealed a negative effect of PtMYB1 on PpAS1 expression. The potential role of MYB factors in the transcriptional regulation of PpAS1 in vascular cells is discussed.